Kinetics of Manganese Oxidation by Cell-Free Extracts of Bacteria Isolated from Manganese Concretions from Soil - Douka, Catherine E. (1980)
A study of the kinetics of Mn(2+) oxidation catalyzed by cell extracts of two bacterial isolates (E(1), Pseudomonas III [new isolate] and E(4), Citrobacter freundii) isolated from the core of manganese concretions from Greek soils is presented. The reaction velocity of Mn(2+) oxidation was determined from the rate of consumption of Mn(2+). The oxidation of Mn(2+) was followed by measuring changes in Mn(2+) concentration by activation analysis and by atomic absorption spectrophotometry. The reaction velocity was directly proportional to cell extract concentration when the reaction time was 1 h. At longer reaction times, the relationship deviated from linearity because substrate concentration became limiting. The rate of Mn(2+) oxidation increased with the Mn(2+) concentration. Analysis of the results by application of the integrated Michaelis equation for determining Michaelis constants and maximal velocities either in the presence (K(m) = 3.33 μmol/ml and V(max) = 1.25 μmol/ml·h) or in the absence of maleate buffer (K(m) = 2.52 μmol/ml and V(max) = 2.04 μmol/ml·h) indicated a strong affinity between the oxidizing system and manganese. All results in this study are consistent with an enzymatic manganese-oxidizing system and give an indication of the mechanism of biological Mn(2+) oxidation in soil which differs from that in the marine environment.